Global Benchmarking of Marketing Doctoral Program Faculty and Institutions by Subarea. (April 2014) - Elbeck, Matt; Vander Schee, Brian A.
This study benchmarks marketing doctoral programs worldwide in five popular subareas by faculty and institutional scholarly impact. A multi-item approach identifies a collection of top-tier scholarly journals for each subarea, while citation data over the decade 2003 to 2012 identify high scholarly impact marketing faculty by subarea used to benchmark and compare faculty and programs globally. The major findings include top-tier journal collections in five popular doctoral program marketing subareas, the dominance of U.S.-based marketing scholars, and the scholarly inroads of northern European programs. The findings offer insight for a number of stakeholders, including potential doctoral students, faculty recruitment and retention, and institutional image building.